Eye movements reset visual perception - Paradiso, M. A.; Meshi, D.; Pisarcik, J.; Levine, S. (Journal of vision (Charlottesville, Va.), 2012)
Human vision uses saccadic eye movements to rapidly shift the sensitive foveal portion of our retina to objects of interest. For vision to function properly amidst these ballistic eye movements, a mechanism is needed to extract discrete percepts on each fixation from the continuous stream of neural activity that spans fixations. The speed of visual parsing is crucial because human behaviors ranging from reading to driving to sports rely on rapid visual analysis. We find that a brain signal associated with moving the eyes appears to play a role in resetting visual analysis on each fixation, a process that may aid in parsing the neural signal. We quantified the degree to which the perception of tilt is influenced by the tilt of a stimulus on a preceding fixation. Two key conditions were compared, one in which a saccade moved the eyes from one stimulus to the next and a second simulated saccade condition in which the stimuli moved in the same manner but the subjects did not move their eyes. We find that there is a brief period of time at the start of each fixation during which the tilt of the previous stimulus influences perception (in a direction opposite to the tilt aftereffect)--perception is not instantaneously reset when a fixation starts. Importantly, the results show that this perceptual bias is much greater, with nearly identical visual input, when saccades are simulated. This finding suggests that, in real-saccade conditions, some signal related to the eye movement may be involved in the reset phenomenon. While proprioceptive information from the extraocular muscles is conceivably a factor, the fast speed of the effect we observe suggests that a more likely mechanism is a corollary discharge signal associated with eye movement.